2017
DOI: 10.7860/jcdr/2017/26422.9811
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Knowledge Related to the Emergency Management of Avulsed Tooth amongst the Medical Practitioners of Nagpur, Central India

Abstract: Regardless of the level of education, the general medical practitioners of Nagpur lack most of the knowledge required for the emergency management of an avulsed teeth. Keeping the in mind the present scenario, it was recommended that education regarding avulsed tooth should be incorporated in school and medical curriculum to increase awareness among parents, teachers and medical practitioners. Also, it is the responsibility of the dentist to make the society aware of this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…In question 2, compared with pulpotomy, pulpectomy requires less cooperation by the child. Second, studies from different countries have demonstrated a low‐to‐moderate knowledge level of dentists regarding dental trauma 30,34‐36 . Possible explanations for these discrepancies could be economic, population‐based, and diversities in oral health policy in various countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In question 2, compared with pulpotomy, pulpectomy requires less cooperation by the child. Second, studies from different countries have demonstrated a low‐to‐moderate knowledge level of dentists regarding dental trauma 30,34‐36 . Possible explanations for these discrepancies could be economic, population‐based, and diversities in oral health policy in various countries.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies from different countries have demonstrated a low-to-moderate knowledge level of dentists regarding dental trauma. 30,[34][35][36] Possible explanations for these discrepancies could be economic, population-based, and diversities in oral health policy in various countries. The differences in methodology and study design should also be considered when comparing the knowledge level of dentists in different studies.…”
Section: Question Descriptionmentioning
confidence: 99%
“…The present study revealed data about the knowledge of students in dentistry, nursing, and medical degree programs regarding the avulsion of permanent teeth. In recent decades, studies have reported a lack of knowledge about dental avulsion by professionals already working in the health field [9,[19][20][21][22][23][24][25][26]. However, there is still a shortage in the literature in relation to the level of knowledge and the main emergency procedures for handling a case of tooth avulsion, among students of courses in the health field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their technical-scientific knowledge and the experience gained in treating cases of tooth avulsion, dentists have other fundamental roles in society: namely, those of preventing its occurrence and participating in the education of the population. Only the integration of these factors could have a positive influence on the prognosis of tooth reimplantation (Manfrin et al, 2007;Kumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%